Translanguaging for Transformation: Identity, Equity, and Pedagogical Resistance in Nepalese ELT Classrooms - Khem Raj Rauteda (Indonesian Journal of English Language Studies (IJELS), 2025)
Translanguaging refers to the dynamic, natural, and purposeful mixing of multiple languages in communication. It has become popular among English language teachers in multilingual settings. It promotes learner agency and acknowledges individual identities and experiences. However, some teachers still mistakenly view multilingualism as a barrier rather than an asset in English Language Teaching (ELT). Despite the advantages of translanguaging in ELT, little empirical research has been done on its use in Nepalese ELT classrooms, especially when it comes to the teachers' perspectives. The study aims to investigate the roles of translanguaging in ELT classrooms and to analyze the teachers' experience of using translanguaging in ELT classrooms. Employing the phenomenological research design, the researcher purposively selected three English language teachers teaching in three different public schools in the Sunsari district for in-depth interviews. The interviews were recorded, transcribed, coded, categorized, and analyzed thematically. The study found that teachers affirm students' identities and promote an inclusive learning environment by using translanguaging as a transformative tool. The study additionally shows how teachers challenge the exclusive English and mix multiple languages to create a translingual space that empowers students and fosters equity in the classroom. The study concluded that translanguaging is a flexible approach to ELT that enhances student engagement and understanding of content. It implies that teachers in multilingual contexts adopt a translingual pedagogical approach to embrace diversity, promote social justice, and empower their students.